2017
DOI: 10.1186/s12883-017-0970-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Homocysteine on white matter diffusion parameters in Alzheimer’s disease

Abstract: BackgroundThe clinical features of Alzheimer’s disease (AD) are related to brain network degeneration, and hyperhomocysteinemia is related to greater white matter hyperintensities. We investigated the changes in four diffusion tensor imaging parameters in the white matter of patients with early stage AD, examined their associations with homocysteine level, and tested the clinical significance of the diffusion tensor imaging parameters and homocysteine level in correlation analysis with cognitive test scores.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Several studies have shown the association between WMH and blood levels of molecules, such as cystatin C (CysC), 25‐hydroxyvitamin D and homocysteine, and the presence of lifestyle‐associated diseases, such as hypertension, hyperlipidemia and diabetes mellitus . However, most of these studies have assessed WMH by visual rating, which is not very precise .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown the association between WMH and blood levels of molecules, such as cystatin C (CysC), 25‐hydroxyvitamin D and homocysteine, and the presence of lifestyle‐associated diseases, such as hypertension, hyperlipidemia and diabetes mellitus . However, most of these studies have assessed WMH by visual rating, which is not very precise .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown the association between WMH and blood levels of molecules, such as cystatin C (CysC), 25-hydroxyvitamin D and homocysteine, and the presence of lifestyleassociated diseases, such as hypertension, hyperlipidemia and diabetes mellitus. [8][9][10] However, most of these studies have assessed WMH by visual rating, which is not very precise. [3][4][5] In the present study, we calculated the volume of periventricular hyperintensities (PVH) and deep WMH (DWMH) on T2 fluid-attenuated inversion recovery (FLAIR) MRI using 3D Slicer, a freely available, opensource software package for visualization, registration, segmentation, and quantification of medical data (http://www.slicer.org).…”
Section: Introductionmentioning
confidence: 99%
“…This is corroborated by a direct association between annual 25(OH)D increase and ALIC volumes at follow-up. While previous studies have linked vitamin D and folate deficiency to WM damage (Sachdev et al, 2002;Bleich and Kornhuber, 2003;Den Heijer et al, 2003;Dufouil et al, 2003;Scott et al, 2004;Censori et al, 2007;De Lau et al, 2009;Pieters et al, 2009;Buell et al, 2010;Prager et al, 2014;Annweiler et al, 2015b;Del Brutto et al, 2015;Moon et al, 2015;Wu et al, 2015;Lee et al, 2017), our study further specified most affected ROIs and target socio-demographic groups. The ALIC connects the thalamus with the frontal lobe, suggesting these nutrients can maintain cognitive functions that are reliant on frontothalamic connectivity, such as executive function (Schoenberg and Scott, 2011;Jacobs et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Novel are our findings that folate and 25(OH)D are related to greater white matter integrity, with folate being inversely related to MD in the ALIC region while 25(OH)D being related to higher FA in the cingulum (cingulate gyrus). While previous studies have linked vitamin D and folate deficiency to WM damage (Sachdev et al, 2002;Bleich and Kornhuber, 2003;Den Heijer et al, 2003;Dufouil et al, 2003;Scott et al, 2004;Censori et al, 2007;De Lau et al, 2009;Pieters et al, 2009;Buell et al, 2010;Prager et al, 2014;Annweiler et al, 2015b;Del Brutto et al, 2015;Moon et al, 2015;Wu et al, 2015;Lee et al, 2017), our study further specified most affected ROIs and target socio-demographic groups. The ALIC connects the thalamus with the frontal lobe, suggesting these nutrients can maintain cognitive functions that are reliant on frontothalamic connectivity, such as executive function (Schoenberg and Scott, 2011;Jacobs et al, 2013).…”
Section: A Corrigendum Onmentioning
confidence: 99%